2023
DOI: 10.1209/0295-5075/acaac5
|View full text |Cite
|
Sign up to set email alerts
|

The nonlinear effects and applications of gain doped whispering-gallery mode cavities

Abstract: Whispering gallery mode (WGM) cavities formed by dielectric structures have attracted intensive interest in various fields. The high-quality factor and smaller mode volume associated with the optical modes have inspired experiments in nonlinear optics, nanophotonics, and quantum information science. Moreover, it also gives rise to optical biosensors and other significant applications. To further reduce the material loss of the resonator, optical gain materials, such as erbium and ytterbium, are doped into the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…This effect arises due to quantum interference between distinct excitation pathways in the atomic system, and is referred to as electromagnetically induced transparency (EIT). EIT has found extensive use in the study of light-matter interactions, owing to its noteworthy quantum coherent properties [2][3][4][5][6][7]. EIT is particularly relevant for diverse applications, including slow light [8][9][10], the creation of a significant nonlinear response [11,12], the generation of an electromagnetically induced grating (EIG) [13][14][15][16][17][18] and other related phenomena [5,[19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect arises due to quantum interference between distinct excitation pathways in the atomic system, and is referred to as electromagnetically induced transparency (EIT). EIT has found extensive use in the study of light-matter interactions, owing to its noteworthy quantum coherent properties [2][3][4][5][6][7]. EIT is particularly relevant for diverse applications, including slow light [8][9][10], the creation of a significant nonlinear response [11,12], the generation of an electromagnetically induced grating (EIG) [13][14][15][16][17][18] and other related phenomena [5,[19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…EIT has found extensive use in the study of light-matter interactions, owing to its noteworthy quantum coherent properties [2][3][4][5][6][7]. EIT is particularly relevant for diverse applications, including slow light [8][9][10], the creation of a significant nonlinear response [11,12], the generation of an electromagnetically induced grating (EIG) [13][14][15][16][17][18] and other related phenomena [5,[19][20][21][22][23][24][25]. Recent studies have observed the EIG phenomenon in atomic systems, quantum wells, and quantum dots [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…indices [10], and others [7,[11][12][13][14] all heavily rely on coherent medium. Using atomic systems, in addition to a single EIT, numerous EIT windows have been seen using a variety of atom-field configurations, including multi-levels atomic media [15][16][17][18][19][20][21]. Since there are many EIT windows, it is possible to transmit light simultaneously at various frequencies, which has potential uses in optical signal processing [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The staircase technique is a very common numerical method that is employed for such cases. In a recent paper, an on-chip Luneburg lens was applied through the integration of gradient Si waveguides and metamaterial structures [16][17][18][19][20][21][22][23]. In order to achieve the gradient index distribution, the filling ratio mapping of Si nanorods was utilized.…”
Section: Introductionmentioning
confidence: 99%